2011
DOI: 10.2486/indhealth.ms1219
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Work Environments on Thermal Strain on Workers in Commercial Kitchens

Abstract: The purpose of this study was to clarify the effect of working environments of different kinds of commercial kitchens on the thermal strain of kitchen workers. This study design was cross-sectional study, and data collection was performed during busy time in commercial kitchen from August to September 2006. The research subjects were 8 institutions, involving 7 cookers, and 16 men. Measured environmental variables were air temperature, radiant heat index, wet bulb globe thermometer index (WBGT) in front of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…It was shown that the type of the cooker used has a significant influence on the air temperature in such indoor area. If electric cookers are used, the air temperature inside the building observed during the research was higher than for gas cookers (Matsuzuki et al 2011 ).…”
Section: Air Quality In Various Types Of Food Cooking Areas/placesmentioning
confidence: 92%
“…It was shown that the type of the cooker used has a significant influence on the air temperature in such indoor area. If electric cookers are used, the air temperature inside the building observed during the research was higher than for gas cookers (Matsuzuki et al 2011 ).…”
Section: Air Quality In Various Types Of Food Cooking Areas/placesmentioning
confidence: 92%
“…While during the meal preparation time in both pantry car kitchen, chefs are using common cooking equipment like; heater or gas, oven, kettle, and soup warmer, etc. These devices produce heat and humidity during food preparation, due to which the indoor environment of the pantry car becomes hot and humid [14]. Which, creates a harmful work environment for chefs and directly impacts work efficiency and performance.…”
Section: Introductionmentioning
confidence: 99%
“…While preparation of the meal these types of instrument leads to humidity, fumes and heat generation. Because of this, the indoor environment of a pantry car kitchen becomes severely hot and humid [7]. The existing hot and humid conditions cause excessive sweating and make chefs work difficult in a pantry car, which is not conducive to human work.…”
Section: Introductionmentioning
confidence: 99%